Positive and neutral updating reconsolidate aversive episodic memories via different routes - Wang, Jingyi (2021)
Aversive memories are long-lasting and prone to burden our emotional wellbeing and mental health. Yet, how to remedy the maladaptive effects of aversive memories remains elusive. Using memory reactivation and emotional updating manipulations, we investigated how positive and neutral emotion may update aversive memories for reconsolidation in humans. We found that positive updating after reactivation was equivalent to neutral updating in impairing true memories of a previous aversive event after a 12-hour wakeful delay, but induced more false memory. Moreover, additional 12-hour delay with overnight sleep did not further enlarge true memory differences, but attenuated the effect of reactivation and updating on false memory. Interestingly, the neutral rather than the positive updating reduced the emotional arousal of the aversive memory 24 h later. Our findings could serve as a reference for real-world therapeutic applications regarding how positive and neutral updating may reshape aversive memories, especially when taking wake- and sleep-filled reconsolidation into account.